Aplikasi Pencarian Pemandu dan Pendaki Gunung di Indonesia Berbasis Web - Aldi Rezaldi; Henri Septanto (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The purpose of this research is to develop a web that makes it easy for guides and climbers to connect with each other and can make the process of climbing together. Climbers can find a guide by posting the climbing form and the guide can find climbers by submitting guides on the climbing posts of the climber. The author uses the RUP (Rational Process Unified) method to analyze and design systems with UML (Unified Modeling Language) modeling. The system was built using Visual Studio Code software as a code editor, PHP as a programming language, PHP MyAdmin as a database, Laravel as a framework and XAMPP as a web server. The final result of the expected research is the Web-Based Mountain Guides and Guides Search Application.